Factors influencing adherence to non-communicable disease medication in India: secondary analysis of cross-sectional data from WHO - SAGE2 - Abraham Tolley; Kirpal Grewal; Alessa Weiler; Anna Maria Papameletiou; Refaat Hassan; Saurav Basu (Frontiers in Pharmacology, 2023)
Background: Non-communicable diseases (NCDs) are a leading cause of death globally and disproportionately affect those in low- and middle-income countries lower-middle-income countries. Poor medication adherence among patients with NCDs is prevalent in India due to lack of initiation, missed dosing or cessation of treatment, and represents a growing healthcare and financial burden.Objective: This study aimed to identify factors influencing medication adherence in adults with NCDs in India.Methods: We performed a cross-sectional study, conducting secondary data analysis on the second wave of the World Health Organisation’s ‘Study on global AGEing and adult health (SAGE)’, a survey that collected data from predominantly older adults across India. Bivariate analysis and multivariate logistic regression modelling were conducted to specifically interrogate the reasons for lack of initiation and cessation of treatment. Reporting of this study was informed by the STROBE guidelines.Results: The average medication adherence rate was 51% across 2,840 patients with one or more NCDs, reflecting non-initiation and lack of persistence of treatment. The strongest factor significantly predicting non-adherence to medication across these components was multimorbidity (odds ratio 0.47, 95% CI 0.40–0.56). Tobacco use (OR = 0.76, CI 0.59–0.98) and never having attended school (OR = 0.75, CI 0.62–0.92) were significantly associated with poor medication adherence (p < 0.05) while rural living (OR = 0.70, CI 0.48–1.02), feelings of anxiety (OR = 0.84, CI 0.66–1.08) and feelings of depression (OR = 0.90, CI 0.70–1.16) were factors lacking statistically significant association with medication adherence on multivariate analysis. Older age (OR = 2.02, CI 1.51–2.71) was significantly associated with improved medication adherence whilst there was a weak association between increased wealth and improved medication use.Limitations: The SAGE2 survey did not capture whether patients were taking their medication doses according to prescribed instructions—as a result our findings may under-estimate the true prevalence of medication non-adherence.Conclusion: Our analysis provides evidence that poor medication adherence in India is multifactorial, with distinct socioeconomic and health-system factors interacting to influence patient decision making. Future large-scale surveys interrogating adherence should assess all components of adherence specifically, whilst public health interventions to improve medication adherence should focus on barriers that may exist due to multimorbidity, comorbid depression and anxiety, and low educational status.